First-principles investigations for the hydrogen storage properties of XVH3 (X=Na, K, Rb, Cs) perovskite type hydrides - Xu, Nanlin; Chen, Yan; Chen, Shanjun; Zhang, Weibin; Li, Song; Song, Ruijie; Zhang, Jingyi (Journal of materials research and technology, 2023)
The structural, mechanical, electronic, kinetic, thermodynamic, optical and hydrogen storage properties of new perovskite hydrides XVH3 (X = Na, K, Rb, Cs) were investigated using density functional theory (DFT). The calculation of formation energy and elastic constants shows that the XVH3 compounds have thermodynamic and mechanical stability. The calculation of the B/G ratio revealed that these hydrides are brittle materials. Furthermore, the bonding type of these hydrides was found to be closer to ionic bonding. These compounds were found to be insulators with ferromagnetic properties in terms of their electronic properties. Furthermore, Bader partial charge analysis was utilized to investigate their charge transfer properties. The optical properties analysis demonstrated that these hydrides exhibit high absorption rates in ultraviolet region. The dynamic stability of these crystals was determined by analyzing their phonon dispersion curves, also their thermodynamic properties, including heat capacity, entropy, energy and free energy as a function of temperature, were studied. Furthermore, this study investigated the hydrogen storage capacity of XVH3 compounds. The results indicated that NaVH3, KVH3, RbVH3 and CsVH3 had hydrogen storage capacities of 3.78, 3.15, 2.12 and 1.59 wt%, respectively. This study is the first to explore XVH3 perovskite hydrides and provides new potential hydrogen storage material options.